Poldark. The complete second season [videorecording (DVD)] - Turner, Aidan, 1983-; Tomlinson, Eleanor, 1992-; Bentall, Ruby, 1988-; Graham, Winston (PBS Distribution, 2016)
Poldark, the drama that has become a cultural phenomenon, continues for a second season on the stunning beaches of Cornwall. It's 1790 and there is riot and revolution in the air. Ross Poldark, the character redefined by the smoldering Aidan Turner, must fight for his freedom when George Warleggan tries to have him hanged as a revolutionary. While Francis and Elizabeth watch on in horror, can Demelza save Ross from himself?